How does social sustainability feature in studies of supply chain management? A review and research agenda. Issue 6 (11th September 2017) - Nakamba, Christine Chanda; Chan, Paul W.; Sharmina, Maria
Abstract : Purpose: The purpose of this paper is to examine how social sustainability is considered in the study of supply chain management, thereby identifying key areas for future researchers to develop. Design/methodology/approach: A systematic literature review of 109 studies is conducted. The papers have been analysed with a particular focus on their definition of social sustainability, research methods used, the central themes covered and the evolution of the debate including theories and the main findings. Findings: Findings show that, first, researchers have thus far focused on principles for managing social change, developing measures for performance, identifying drivers and barriers, with few studies considering the social practices, particularly at the micro level and in the context of small and medium-sized enterprises. Second, findings also reveal that there is less consideration of the suppliers', as opposed to the buyers', perspective. Research limitations/implications: This review focuses only on social sustainability within supply chain management, without considering the economic and environmental dimensions. Practical implications: This review provides the key themes and areas for managers/practitioners to consider when implementing social sustainability in supply chains. It also provides insights into under-researched areas together with the need for future researchers to move beyond frameworks and develop more tools and instruments for measuring social performance in practice. Originality/value: This paper is one of the few studies that consider the social dimension of sustainability exclusively within the context of supply chains, providing insights and implications for further research.